Comparative Study of Investment Preferences Among Millennial and Gen Z in Ahmedabad - Ravani, Karan; Verma, Harsh; Vidani, Jignesh (International Journal of Economic, Finance and Business Statistics, 2024)
This study investigates the investment preferences of Millennials and Gen Z in Ahmedabad, India, highlighting the distinct financial behaviours and attitudes of these two generational cohorts. Utilizing a mixed-methods approach, the research analyses data collected from 106 respondents, focusing on aspects such as risk tolerance, reliance on digital platforms, and influences on investment decisions. Findings indicate that Millennials exhibit a preference for low-risk investments and traditional financial advice, while Gen Z shows a strong inclination towards new-age assets, such as cryptocurrencies, and is heavily influenced by social media. The study reveals significant differences in investment strategies, underscoring the necessity for financial institutions to tailor their offerings to meet the unique needs of each generation. Furthermore, the research emphasizes the importance of financial literacy and education in empowering young investors. As Millennials and Gen Z increasingly shape the investment landscape, understanding their preferences is essential for fostering responsible financial practices and promoting sustainable investing. This study serves as a foundation for future research aimed at exploring the evolving financial behaviours of these generations.